Проявления специфического процесса у детей и подростков, которые были в контакте с больными химиорезистентным туберкулезом - Мирончук, Ю. В.; Чернышова, Л. И.; Пушнова, О. А.; Субботина, Н. И.; Mironchuk, Ju. V.; Chernyshova, L. I.; Pushnova, O. A.; Subbotina, N. I.; Мирончук, Юлія Валеріївна (My University, 2016)
Изучен характер проявлений специфического процесса у 14 детей и подростков, которые были в контакте с больными химиорезистентным туберкулезом легких. Установлено, что проведение вакцинации БЦЖ и своевременная диагностика виража туберкулиновой пробы у детей и подростков из контакта с больными химиорезистентным туберкулезом легких являются очень актуальными и важными проблемами современной фтизиопедиатрии. Решение этих проблем позволит избежать заболевания детей и подростков мультирезистентным туберкулезом. The character of the manifestations of specific process in 14 children and teens,who have been in contact with patients with drug-resistant tuberculosis was investigated.it has been established, that bcg vaccination and timely diagnosis of turn mantoux test in children and teens from contact with a lungs drug-resistant tuberculosis patients are very actual and important problems of modern phthisiology of children. Resolving of these problems will prevent of children and teens illness from multi-drug-resistant tuberculosis.
Manifestations of specific processes in children and teenswho have been in contact with drug-resistant tuberculosis
Keywords: туберкулез; дети; подростки; контакт с больными химиорезистентным туберкулезом; tuberculosis; children; adolescents; exposure to diseased drug-resistant tuberculosis